2020
DOI: 10.1007/s00405-020-06533-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life through the routine use of the patient concerns inventory for head and neck cancer patients: main results of a cluster preference randomised controlled trial

Abstract: Purpose The patient concerns inventory (PCI) is a prompt list allowing head and neck cancer (HNC) patients to discuss issues that otherwise might be overlooked. This trial evaluated the effectiveness of using the PCI at routine outpatient clinics for one year after treatment on health-related QOL (HRQOL). Methods A pragmatic cluster preference randomised control trial with 15 consultants, 8 ‘using’ and 7 ‘not using’ the PCI intervention. Patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Clinical-effectiveness results of the PCI intervention are published elsewhere [ 12 ] (see Appendix 1 for the summary) and indicated that length of the consultation time had a tendency to reduce with subsequent use of the PCI in comparison with the non-PCI group.…”
Section: Methods and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical-effectiveness results of the PCI intervention are published elsewhere [ 12 ] (see Appendix 1 for the summary) and indicated that length of the consultation time had a tendency to reduce with subsequent use of the PCI in comparison with the non-PCI group.…”
Section: Methods and Designmentioning
confidence: 99%
“…The list serves to guide the outpatient consultation and covers a range of symptoms and potential problems patients may face after treatment. It has been shown to be feasible in routine consultations [ 11 , 12 ] and for wider adoption across a cancer network [ 13 ]. The PCI is freely available online ( http://www.patient-concerns-inventory.co.uk ).…”
Section: Introductionmentioning
confidence: 99%
“…(17) Patients appreciate the opportunity to raise their issues, and inclusion of the PCI is a low-cost intervention which in a randomised trial setting has indicated improvements in QOL and socio-emotional dysfunction. (18) The UW-QOL version 4 consists of 12 domains scaled from 0 (worst) to 100 (best) according to response hierarchy. (16) UW-QOL domains are presented within two subscales, physical function and social-emotional function with each subscale score being the mean of six domain scores.…”
Section: Instrumentsmentioning
confidence: 99%
“…A systematic review and content comparison of unmet needs self-report measures favored the PCI over 13 other tools (Shunmugasundaram et al, 2019). In a randomized trial the PCI has been shown to be a low-cost intervention which is feasible in routine clinical practice and is associated with a positive effect on QoL and socio-emotional dysfunction (Rogers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the PCI can help to identify the frequency of FCR (Rogers et al, 2010a;Kanatas et al, 2012;Ghazali et al, 2013), thus far specific details of which kind of patient is most at risk are lacking. The PCI randomized trial (Rogers et al, 2020) has given an opportunity to evaluate in much greater depth the issue of FCR and this is of particular merit as the trial is based in standard practice and involved 15 consultant HNC surgeons. Hence, the aim of this study is to describe the demographic background and clinical characteristics for those HCN patients who indicate a high level of FCR in their review consultation.…”
Section: Introductionmentioning
confidence: 99%